Studies of Gallium Nitride Electron Mobility Transistors (GaN HEMTs) and GaN Metal-Insulator-Semiconductor (GaN MISHEMT) - Lau, Sien Hui (Nanyang Technological University, 2020)
Gallium Nitride Electron Mobility Transistors (GaN HEMTs) and GaN Metal-Insulator Semiconductor (GaN MISHEMT) is a well-known material since the discovery of its properties due to high thermal operations, high frequency and high power to be applied in the Microfabrication device application. Hence, these materials become significant and magnificent to be used in various types of electronic devices in the semiconductor industry. For instance, GaN HEMTs and GaN MISHEMT are wide to be used in the high-power application such as high power switching application, high radiofrequency device, etc. The purpose of the studies of the GaN HEMTs and GaN MISHEMT are related to the Schottky barrier height for the HEMT structure and the interface trap for the GaN MISHEMTs. Thus, we will apply the analysis characteristics technique like I-V to measure the Schottky barrier height in HEMT structure and C-V analysis technique in MISHEMTs for measuring the interface trap density. The final goal of this project is to reduce the current leakage at the interface trap.